PENGARUH KONFLIK DAN PENGEMBANGAN KARIR TERHADAP KINERJA KARYAWAN PT. SUNSHINE FOOD GROUP INTERNATIONAL PALEMBANG - Yasmina Martini; Ulil Amri (JURNAL KOMPETITIF, 2019)
ABTRACT This study examines conflict and career development on the performance of employees of PT. Sunshine Food Group International Palembang The purpose of this research is to find out and prove whether there is conflict and career development on the performance of the employees of PT. Sunshine Food Group International Palembang, both simultaneously and partially. Research site on POM IX street, Palembang Square Mall area (Siloam Sriwijaya Hospital) Palembang. The population in this study were 35 employees and the census sampling method or saturated sample of the total population was 35 employees. Data collection techniques through the distribution of questionnaires that are closed. Significance level of 5%, data processing media through the SPSS program version 20.0. The results of the analysis of the data obtained correlation (r) between conflict with career development with employee performance of 0.762 which means that the relationship of conflict with career development has a strong and significant relationship, and R2 is 0.581 or 58.10%, while Adjusted (R2) is 0 , 554 or 55.40% variation in Employee Performance and the remaining 44.60% is explained by other factors such as, coordination, education and training and work climate. Multiple linear regression equations: Ŷ = 4.087 + 0.280 X1 + 0.869 X2 + e, F-Test results obtained Fhit value 22,148 with Sig. 0,000, because the value of Sig, F <0.05 proves that conflict and career development affect employee performance. T-test results obtained thit value of 2.081 with Sig.0.045 <0.05 for conflict, thit value of 5.161 with Sig.0.000 <0.05 for career development partially influencing employee performance. Keywords: Conflict, Career Development, Employee Performance